1998
DOI: 10.1093/humrep/13.12.3434
|View full text |Cite
|
Sign up to set email alerts
|

A prospective randomized trial of blastocyst culture and transfer in in- vitro fertilization

Abstract: The effectiveness of blastocyst culture and transfer in human in-vitro fertilization (IVF) was evaluated in a prospective randomized trial in patients having a moderate to good response to gonadotrophin stimulation. Embryos were transferred either on day 3 after culture to around the 8-cell stage in Ham's F-10 medium supplemented with fetal cord serum, or on day 5 after culture to the blastocyst stage in the sequential serum-free media G 1.2 and G 2.2. The pregnancy rates after transfer on day 3 or day 5 were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
304
3
17

Year Published

1999
1999
2004
2004

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 660 publications
(328 citation statements)
references
References 38 publications
4
304
3
17
Order By: Relevance
“…The introduction in 1998 of blastocyst culture caused us to reevaluate our embryo culture and cryopreservation strategy. The initial studies on blastocyst transfer showed that the two possible advantages of blastocyst culture were an improved rate of pregnancy in the fresh cycle and a decrease in high-order multiple pregnancies (14)(15)(16). We sought to determine whether additional strategies could enhance our long-standing approach of cryopreserving extra embryos at the PN-S. We were interested in determining whether this enhanced approach might be an effective alternative to the more commonly used strategy of leaving all embryos in culture for selection of the best embryos at the cleavage or blastocyst stages.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The introduction in 1998 of blastocyst culture caused us to reevaluate our embryo culture and cryopreservation strategy. The initial studies on blastocyst transfer showed that the two possible advantages of blastocyst culture were an improved rate of pregnancy in the fresh cycle and a decrease in high-order multiple pregnancies (14)(15)(16). We sought to determine whether additional strategies could enhance our long-standing approach of cryopreserving extra embryos at the PN-S. We were interested in determining whether this enhanced approach might be an effective alternative to the more commonly used strategy of leaving all embryos in culture for selection of the best embryos at the cleavage or blastocyst stages.…”
Section: Discussionmentioning
confidence: 99%
“…These were higher than those reported in most blastocyst studies even though only 0.88, 0.80, and 0.61 more embryos were cultured for Groups I, II, and III, respectively, than the number transferred. Pregnancy and implantation rates with blastocyst transfer have ranged from 21 to 77% and 9-62%, respectively (2,5,6,(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28). With blastocyst transfer, all embryos are retained in culture to ensure at least two high-quality blastocysts are available for transfer.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations